Diversity of hydrobionts in delta of the Ile river in changing human impact (Eurasian Journal of Ecology, 2020)
Delta of the Ile River is one of the biggest wetlands of Asia. State of ecosystems of the delta andadjacent territories was reported as threatened about 30 years ago. Eastern part of the delta was includedin protected area of the Ili-Balkhash State Nature Reserve in 2018 only. Analysis the modern diversity ofwater organisms was the aim of our investigation. Samples collecting had been done in spring and summer 2019 with common methods of hydrobiological investigations. Different kinds of habitats like river,floodplain lakes and the lakeside were investigated. High concentrations of ammonia were revealed indifferent part of the delta as well as in the lake in spring. Checklist of phytoplanktons, zooplanktons andbenthos consisted from 31, 2 and 12 species respectively. Fishes were presented with 16 alien species;between them 6 short living and noncommercial fish species were the most common in the delta. Themodern diversity of hydrobionts is much less in contrast to the period before strong human impact, andindicate poor state of water ecosystems of the delta. The obtained data is started point for long termmonitoring and assessment of effectiveness of wildlife management and actions for rehabilitations ofnatural ecosystems of the Ile delta.Key words: delta of the Ile River, hydrobionts, plankton, benthos, ichthyofauna.